2021
DOI: 10.1111/rec.13374
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient‐use strategy and not competition determines native and invasive species response to changes in soil nutrient availability

Abstract: Non-native invasive plants often outcompete native species under high resource availability. Restoration techniques that lower resources may, therefore, create favorable conditions for resource conservative native species over resource exploitative invasive species. Research on this topic has focused on temperate grass and forb-dominated ecosystems and has rarely been tested for woody species or tropical vegetation. We evaluated growth, resource-use efficiency (RUE), ecophysiology, and competition (i.e. a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
2
8
1
Order By: Relevance
“…Although the nutrient concentrations that drove these effects are significantly higher (approximately 20-fold) than typically occur in these plots after feral ungulate disturbance (Long et al 2017), this is still significant given that regeneration is a key aspect of restoration and a critical filter for invasive species success and community assembly. This finding is also consistent with previous observations that M. polymorpha, a dominant native overstory tree, showed greatly reduced growth and survival under high nutrient conditions in our greenhouse study (Knauf et al 2021), as well as with fertilizer additions applied in situ in N-limited wet montane forests (Ostertag & Verville 2002). These results collectively support the idea that resource manipulation can have complex effects on ecosystems, with elevated nutrient supply negatively affecting some dominant native species adapted to low-resource environments.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Although the nutrient concentrations that drove these effects are significantly higher (approximately 20-fold) than typically occur in these plots after feral ungulate disturbance (Long et al 2017), this is still significant given that regeneration is a key aspect of restoration and a critical filter for invasive species success and community assembly. This finding is also consistent with previous observations that M. polymorpha, a dominant native overstory tree, showed greatly reduced growth and survival under high nutrient conditions in our greenhouse study (Knauf et al 2021), as well as with fertilizer additions applied in situ in N-limited wet montane forests (Ostertag & Verville 2002). These results collectively support the idea that resource manipulation can have complex effects on ecosystems, with elevated nutrient supply negatively affecting some dominant native species adapted to low-resource environments.…”
Section: Discussionsupporting
confidence: 93%
“…The reasons for the apparent disconnect between strong growth reductions of non‐native invasives in response to C amendment observed in a greenhouse setting (Knauf et al 2021) and the field results reported here are not entirely clear. However, there are several potential explanations.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations